The Manfred Max-Neef Thinking: A Deep Economy Rooted in the Eco-philosophical Perspective of the Deep Ecology - Olmedo, Clara; Ceberio de León, Iñaki (The Trumpeter)

(untitled) (Athabasca University Press, 2022)
In this article, we advance preliminary theoretical reflections on Manfred Max Neef’s thoughts related to the human scale development. From an and transdisciplinary perspective, we argue that Max-Neef moves beyond the field of Ecological Economics towards developing a Deep Economic framework, linked to the Deep Ecology framework outlined by the Norwegian philosopher Arne Næss. We elaborate our argument around two dimensions: a) Biocentrism, based on the conviction that ecology is not limited to reflections and actions toward a balanced and healthy environment to achieve humans´ well-being, but involves all forms of life and ecosystems. b) The intrinsic value of life, a complex idea that Max-Neef expressed in his conviction that the “reverence for life” cannot be solely subjected to human economic activity or interest. Biocentrism and the intrinsic value of life must be approached from a transdisciplinary and organic perspective that demands a dialogue between science-academics, non-combining reason with intuition, ethics, and beauty. this way, these two dimensions become principles that articulate Max-Neef´s Deep Economy, different to other critical approaches in the field of economics.